Genetically-encoded sensors to detect fatty acid production and trafficking - Emilio P. Mottillo; Huamei Zhang; Alexander Yang; Li Zhou; James G. Granneman (Molecular Metabolism, 2019)
Objective: Fatty acids are important for biological function; however, in excess, they can cause metabolic dysregulation. Methods to image and detect fatty acids in real time are lacking. Therefore, the current study examined the dynamics of fatty acid trafficking and signaling utilizing novel fluorescent and luminescent approaches. Methods: We generated fluorescent and luminescent-based genetically-encoded sensors based upon the ligand-dependent interaction between PPARα and SRC-1 to image and detect cellular dynamics of fatty acid trafficking. Results: The use of a fluorescent sensor demonstrates that fatty acids traffic rapidly from lipid droplets to the nucleus. Both major lipases ATGL and HSL contribute to fatty acid signaling from lipid droplet to nucleus, however, their dynamics differ. Furthermore, direct activation of lipolysis, independent of receptor-mediated signaling is sufficient to promote lipid droplet to nuclear trafficking of fatty acids. A luminescent-based sensor that reports intracellular fatty acid levels is amenable to high-throughput analysis. Conclusions: Fatty acids traffic from lipid droplets to the nucleus within minutes of stimulated lipolysis. Genetically-encoded fluorescent and luminescent based sensors can be used to probe the dynamics of fatty acid trafficking and signaling. Keywords: Lipolysis, Brown adipocyte, Lipid droplet, Luminescent sensor, Fluorescent sensor, Fatty acid